The Functioning of Partnership Sales Network as an Effect of the Evolution of Outsourcing in Poland - Lukasz BRZEZINSKI; Magdalena Krystyna WYRWICKA (Communications of International Proceedings, 2021)
Entrusting other entities with performing other tasks within an organisation was already popular in 18th C., the times of craftsmen. The issue of specialisation and competitive edge gained importance as society and technology advanced. In early 21st C. outsourcing was treated as a strategic method of shaping the structure of economic activity. The concept of outsourcing initially applied to a limited scope of decision-making competences on the possibility of introducing changes to the entrusted tasks. Now, however, in the context of outsourcing of sales processes, which form the conceptual basis of the operation of partnership sales networks, it has been connected with the ideas of cooperation, strategic alliance, partnering, shared resources and contracting. A partnership sales network constitutes an alternative or combined solution - a supplementation - with regard to own sales networks. This is a structure made from entities which perform sales tasks for the ordering enterprise (the client) and use its resources, but are not directly a part of the enterprise's organisational structure and its remuneration is usually commission-based. The most important motives for launching partnership sales networks include: increasing the rate at which products and services reach buyers, achieving competitive edge in the future, increasing the enterprise's growth dynamics, reducing the enterprise's costs, increasing the rate at which the organisation's activities adapt to the market's needs, maintaining or improving market position and increasing sales profitability. The aim of the article is to describe the essence of the functioning of partner sales networks on the example of companies from the telecommunications industry.
Keywords: Partnership sales networks; outsourcing of sales processes; evolution of outsourcing; functioning of partnership sales networks